2014
DOI: 10.1002/anie.201404622
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Catalyzed Lysine Side Chain Modification

Abstract: Catalysis of covalent modification of aliphatic amine groups, such as the lysine (Lys) side chain, by nucleic acids has been challenging to achieve. Such catalysis will be valuable, e.g., for practical preparation of Lys-modified proteins. We previously reported DNA-catalyzed modification of the tyrosine and serine hydroxyl side chains, but Lys modification has been elusive. In this study, we show that increasing the reactivity of the electrophilic reaction partner by using 5′-phosphorimidazolide (5′-Imp) rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 57 publications
0
8
1
Order By: Relevance
“…[6] For example, CO 2 generated from cellular respiration is expired in part through the reversible formation of ac arbamate between CO 2 and the amino groups of hemoglobin. [7] Furthermore, the reactions of primary and secondary amines with CO 2 are used to captureC O 2 through the formation of az witterion first and then ac arbamate.…”
Section: Introductionmentioning
confidence: 99%
“…[6] For example, CO 2 generated from cellular respiration is expired in part through the reversible formation of ac arbamate between CO 2 and the amino groups of hemoglobin. [7] Furthermore, the reactions of primary and secondary amines with CO 2 are used to captureC O 2 through the formation of az witterion first and then ac arbamate.…”
Section: Introductionmentioning
confidence: 99%
“…These observations indicate the need to improve our selection strategy to disallow the survival of DNA sequences that catalyze their own glycosylation rather than modification of the intended peptide substrate. In previous studies, we have initially found unanticipated DNA-catalyzed reactivity and then resolved the issue to achieve our initial goal; e.g., refs 13 and 14.…”
mentioning
confidence: 92%
“…( A ) General representation of DNAzyme catalyzed ligation reactions. A nucleophile (e.g., an RNA 2′-OH, a terminal 3′-OH, hydroxyl groups of serine and tyrosine, or an amine) located on a substrate attacks an electrophilic position (e.g., 5′-triphosphate, 5′-phosphorimidazolide) located on the second substrate with the concomitant eviction of a leaving group; ( B ) Catalyzed ligation reaction by hydrolysis of a phosphoramidate bond [162]; ( C ) DNAzyme catalyzed nucleophilic attack of an amine group of a lysine residue on a 5′-phosphorimidazolide unit [172]. …”
Section: Dnazymes Catalyzing Bond Formationmentioning
confidence: 99%